ACTION SPACE PELAKU PERJALANAN PENGGUNA SEPEDA MOTOR - Adinegoro, Lukita; Joewono, Tri Basuki (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Action space refers to a group of locations that an individual visits a limited space and time. The aim of this study is to describe the characteristics and pattern of the space action among travelers who uses motorcycle. The analysis showed that most of the respondents have an activity as much as 11-20 events per day, where higher average appears on Sunday. Most of respondents have travel distanceas much as 20 to 29.9 km. The pattern of action space are found as ellipses as much as 87 %. Most of respondents have an area of travel wide as much as 10-19.9 km², where distance of the center of activities from home ranges from one to five kilometers.